Jews and Anti-Judaism in the New Testament : decision points and divergent interpretations - Donaldson, Terence L.; Society for Promoting Christian Knowledge (Great Britain) (London : SPCK, Society for Promoting Christian Knowledge ; Waco, Tex. : Baylor University Press, 2010)
Jews and Anti-Judaism in the New Testament offers a guide to the issues of anti-Semitism, anti-Judaism, and supersessionism in the New Testament. Combining navigation of the relevant literature--both classics of the field and more recent forays--with exegetical analysis of the Christian canon, Terence L. Donaldson maps the major New Testament writings across three axes: self-definition, degree of separation, and rhetorical intent. --From publisher's description.
Introduction -- Matthew -- Luke-Acts -- John -- Paul -- The New Testament : then and now.
Includes bibliographical references (p. 160-165) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Judaism (Christian theology) -- Biblical teaching; Jews in the New Testament; Christianity and antisemitism -- Biblical teaching